TYPES OF DISCOURSE IN THE PROFESSIONAL COMMUNICATION - Mamirova Gulnoza Ikrom qizi (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with discourse types in the formation of discourse competence. The undergraduates of the higher education establishments face to some difficulties while taking part at real communication processes, receiving the foreign speech, using the foreign speech norms because of not knowing the discourse types. This means that students don’t have discursive competence and in the article here analyzed this very problem and the suggestions about their solvation as well. Formation the discursive competence of the future specialists can help them not only to read and translate the text in target language but to use the very information in their speech.